2021
DOI: 10.1002/dneu.22805
|View full text |Cite
|
Sign up to set email alerts
|

Region‐specific sex modulation of central oxytocin receptor by gut microbiota: An ontogenic study

Abstract: Oxytocin (OT) is a developmentally important neuropeptide recognized to play a dominant role in social functioning and stress‐related behaviors, in a sex‐dependent manner. Nonetheless, the underlining factors driving OT and OT receptor (OTR) early brain development remain unclear. Recent evidence highlight the critical influence of gut microbiota and its bidirectional interaction with the brain on neurodevelopment via the gut microbiota‐brain axis. Therefore, we aimed to determine the impact of gut microbiota … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The microbiota effect on MOPr binding was restricted to male rats, and the presence of sex differences in the microbiome‐gut‐brain axis is in agreement with multiple studies (Coretti et al, 2017; Davis et al, 2017; Leclercq et al, 2017; Sylvia et al, 2017). This sex‐dependent microbiota effect is consistent with our recent findings demonstrating an identical oxytocin receptor density regulation pattern in male GF rats (Effah et al, 2021). The mechanism underlining the increased sensitivity of microbiota regulation of MOPr in males and its resistance in females remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The microbiota effect on MOPr binding was restricted to male rats, and the presence of sex differences in the microbiome‐gut‐brain axis is in agreement with multiple studies (Coretti et al, 2017; Davis et al, 2017; Leclercq et al, 2017; Sylvia et al, 2017). This sex‐dependent microbiota effect is consistent with our recent findings demonstrating an identical oxytocin receptor density regulation pattern in male GF rats (Effah et al, 2021). The mechanism underlining the increased sensitivity of microbiota regulation of MOPr in males and its resistance in females remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…For detailed justification of the selection of these specific age groups as well as for the selection of the GF model, rather than the antibiotic‐treated one to assess the impact of gut microbiota on MOPr ontogeny, the reader is directed to our recent publication (Effah et al, 2021) and the discussion of this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there were no significant differences between conventional (CONV) and germ‐free (GF, animals raised without a microbiota) animals 54 . Another study, however, reported an increase of OXTR protein levels in specific cortical regions from male, but not female, GF rats 55 . To date, to the best of our knowledge, it is not known how microbial depletion affects blood Oxt levels.…”
Section: Oxytocin and Oxytocin Receptormentioning
confidence: 92%
“…Do shifts in the gut microbiome following early life insults influence these processes? Interestingly, germ-free male, but not female rats, have higher densities of OTR in the prefrontal cortex and septum as compared to conventionally housed rats ( Effah et al., 2021 ). Rodent species such as prairie voles could also prove to be incredibly useful in these investigations given that they exhibit complex social behaviors (such as pair bond formation) and that the social circuits underlying these behaviors have been well characterized in voles ( Loth and Donaldson, 2021 ; Walum and Young, 2018 ).…”
Section: What Role Do Microglia Play In Shaping Social Neural Circuits?mentioning
confidence: 93%